(untitled) (Iter, 2022)
The Cynic schoool of philosophy represented one of the most peculiar cultural movements in Antiquity. The Cynic philosophers, like the street dogs that gave them their name, were marginal figures in the society of the Greek poleis. However, they were the first to invent the idea of a “citizenship of the world”, i· e., a “cosmopolitism”. The aim of this paper is to study the Cynic concept of cosmopolitism, with a view to determine its positive or negative value in the context of the mentality of the Hellenistic world, and to observe the similarities and differences between that ancient cosmopolitism and the idea of cosmopolitism that emerges from our globalised world.